2017
DOI: 10.1182/blood-2016-07-723148
|View full text |Cite
|
Sign up to set email alerts
|

In utero cytomegalovirus infection and development of childhood acute lymphoblastic leukemia

Abstract: Key Points CMV is prevalent in pretreatment bone marrow from childhood ALL and not in acute myeloid leukemia. In utero infection with CMV is a risk factor for ALL (OR = 3.71, P = .0016) and is more pronounced in Hispanics (OR = 5.90, P = .006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 23 publications
2
86
0
Order By: Relevance
“…Risk classification at the moment of diagnosis was based on the National Cancer Institute [31] risk criteria. Patients between 1 and 10 years old and a leukocyte count <50 x 109/L were classified as NCI standard-risk whereas those aged �10 years or a leukocyte count �50 x 109/ L were classified as NCI high-risk.…”
Section: Clinical Data Collection and Risk Classificationmentioning
confidence: 99%
“…Risk classification at the moment of diagnosis was based on the National Cancer Institute [31] risk criteria. Patients between 1 and 10 years old and a leukocyte count <50 x 109/L were classified as NCI standard-risk whereas those aged �10 years or a leukocyte count �50 x 109/ L were classified as NCI high-risk.…”
Section: Clinical Data Collection and Risk Classificationmentioning
confidence: 99%
“…Infections early in life have long been suspected to play a role in the development of childhood acute lymphoblastic leukemia (ALL), in particular B-cell precursor ALL, the most common subtype. Many B-cell precursor ALL cases (e.g., high-hyperdiploidy and ETV6-RUNX1-translocated cases) are initiated in utero (1)(2)(3), and exposure to infections during pregnancy may increase offspring's risk of this intrauterine preleukemic development (4)(5)(6)(7). Furthermore, it has been suggested that a lack of exposure to infections in early childhood can cause an abnormal immune response to infections later in childhood, leading to the transformation of preleukemic cells to leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signs of CMV congenital infection include thrombocytopenia and anemia . Our study did not specifically assess the capacity of hematopoietic progenitors to form megakaryocytic CFUs; however, the circulating platelet counts were not significantly different between CB donors with CMV infection and the control group.…”
Section: Discussionmentioning
confidence: 74%